The effect of the scientific harvest strategy on the achievement of students in the Life Sciences Department To understand plant concepts and develop their analytical thinking - Dr. Mohammed Jasim Abdulameer; Dr. Hazem Jasim Sahib (Journal of College of Education, 2024)
The research aims to identify the effect of the scientific harvest strategy on the students of the Department of Life Sciences’ achievement of plant concepts and the development of their analytical thinking. To achieve the objectives of the research, the researcher developed two null hypotheses in a sample consisting of (117) male and female students in three groups (ABC) of students of the Department of Life Sciences / fourth stage in Course of plant physiology. The researcher divided these three groups into two groups, one of which was the students of the experimental group who studied according to the scientific harvest strategy, and the other was the students of the control group who studied according to the usual method (university lecture) for teaching the subject of plant physiology. The researcher also adopted a ready-made test to measure analytical thinking prepared by Al-Mahdawi and Kazem 2023, composed by 40 paragraphs and prepare a test To achieve the multiple-choice plant concepts, the number of items reached 25 items. He set behavioral goals within Bloom’s levels of behavioral goals, which amounted to 180 behavioral goals. He prepared 24 teaching plans for the two groups of research students. The experiment lasted three months. After the end of implementing the experiment, the researcher applied the two research tools in the two post-tests, analytical thinking and the achievement test. for plant concepts and corrected the students’ results on the responses of the two tests. The researcher used statistical methods to process the data obtained for the research. The results of the research showed the superiority of the students of the experimental group that studied according to the cognitive harvesting strategy in the achievement test for plant concepts and their analytical thinking in the plant physiology course. The researcher made some recommendations for training students in colleges. Educational for pure sciences To use modern strategies in teaching scientific subjects and proposals to conduct educational studies dealing with other topics to apply this strategy and its results in research procedures.